2023
DOI: 10.1590/2317-1782/20212020334en
|View full text |Cite
|
Sign up to set email alerts
|

Masking release in cortical auditory evoked potentials with speech stimulus

Abstract: Purpose To analyze the effect of masking on the Cortical Auditory Evoked Potential with speech stimulus in young adults. Methods Fourteen individuals aged between 19 and 28 years of both sexes with no hearing loss participated in the study. The Cortical Auditory Evoked Potential examination was performed with synthetic speech stimulus /ba/ simultaneous to Speech Shaped Noise presented under three conditions: steady noise with a 30 dB SPLep intensity (weak steady noise), steady noise with a 65 dB SPLep intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…The studies included were conducted between 2006 and 2023, in Germany, 14 the United Kingdom, 19 China, 15 the United States, 16,17 and Brazil. 18 Regarding the number of study participants, a minimum of 10 and a maximum of 30 individuals of both sexes were found, except for one study, 14 which did not specify the sex of the participants. The studies were conducted with young and adult participants, aged 19 to 55 years, and only one study 16 included elderly subjects.…”
Section: Review Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The studies included were conducted between 2006 and 2023, in Germany, 14 the United Kingdom, 19 China, 15 the United States, 16,17 and Brazil. 18 Regarding the number of study participants, a minimum of 10 and a maximum of 30 individuals of both sexes were found, except for one study, 14 which did not specify the sex of the participants. The studies were conducted with young and adult participants, aged 19 to 55 years, and only one study 16 included elderly subjects.…”
Section: Review Resultsmentioning
confidence: 99%
“…In the quality assessment through the adapted NOS, the scores of the studies ranged from 5 to 7 points, and we identified that out of the six studies analyzed, five [14][15][16][17][18] had high methodological quality and one study 19 was identified as having moderate quality. All evaluated studies had low scores in the sample selection component, for they did not describe the sampling strategy neither did they jusstify the sample size.…”
Section: Review Resultsmentioning
confidence: 99%
See 3 more Smart Citations